2021
DOI: 10.1029/2021tc006827
|View full text |Cite
|
Sign up to set email alerts
|

Sinking Slab Stress and Seismo‐Tectonics of the Indo‐Burmese Arc: A Reappraisal

Abstract: Differing views on the north‐eastern Indian plate subduction and its seismic potential place the subduction process as relict, ceased, creeping, or fully locked, challenging the seismic hazard uncertainty estimates of Indo‐Burmese Arc (IBA) at either extreme. To clear some of these contentions, we re‐examine the state of the IBA stress field using available earthquake faulting mechanism solutions. Our stress inversion results underline the tectonic complexity and emphasize that the stress of this subduction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 84 publications
2
4
0
Order By: Relevance
“…If we consider the along‐strike extent of the Kabaw Fault (>500 km) (Maurin & Rangin, 2009; Morley et al., 2020; Wang et al., 2014; Figure 2), our fitted locking depth (22 km) and the fact that the region has not experienced a significant event at least in the past century (Kundu & Gahalaut, 2012) we conclude that it is capable of hosting M w 7–7.5 events. Our interpretation aligns with stress inversion from local seismicity suggesting that the Kabaw Fault is actively shortening (Earnest et al., 2021) and with oblique‐thrust focal mechanisms in the area which are distinct from other crustal and intraslab earthquakes (Fadil et al., 2023). In any case, lack of moderate interplate seismic activity and our combined geodetic and structural analysis points to the potential of the Indo‐Shan plate boundary to host large earthquakes both on the Indo‐Burma megathrust and the Kabaw Fault.…”
Section: Discussionsupporting
confidence: 87%
“…If we consider the along‐strike extent of the Kabaw Fault (>500 km) (Maurin & Rangin, 2009; Morley et al., 2020; Wang et al., 2014; Figure 2), our fitted locking depth (22 km) and the fact that the region has not experienced a significant event at least in the past century (Kundu & Gahalaut, 2012) we conclude that it is capable of hosting M w 7–7.5 events. Our interpretation aligns with stress inversion from local seismicity suggesting that the Kabaw Fault is actively shortening (Earnest et al., 2021) and with oblique‐thrust focal mechanisms in the area which are distinct from other crustal and intraslab earthquakes (Fadil et al., 2023). In any case, lack of moderate interplate seismic activity and our combined geodetic and structural analysis points to the potential of the Indo‐Shan plate boundary to host large earthquakes both on the Indo‐Burma megathrust and the Kabaw Fault.…”
Section: Discussionsupporting
confidence: 87%
“…4.3b). Similarly, previous stress inversion studies have suggested an oblique-reverse stress regime within the CMB and Sagaing Fault, with a NE-SW oriented compressional stress axis (Earnest et. al, 2021;Maneerat et.…”
Section: Re-activation Of Neogene Structures Beneath the Cmb In A Ne-...supporting
confidence: 71%
“…Our well-constrained centroid depths and focal mechanisms of the intraslab events provide further insights into the along-arc and along-dip variation of deformation mechanisms within the slab. Previous studies have attributed the ~N-S oriented compression along the shallow part of the subducting slab beneath the IMR as a result of the northward drag of the Indian Plate through the lithospheric mantle which manifests as lateral shear within the slab (Le Dain et al, 1984;Ni et al, 1989;Earnest et al, 2021, Maneerat et al, 2022b. We show that when viewed in a locally unfolded slab reference frame, the deeper intraslab events have more a similar mechanism to the shallower events beneath the IMR, albeit with larger oblique thrust component (Fig.…”
Section: Variation Of Intraslab Earthquake Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations